WORKING UNDER STRESS: AN ANALYSIS OF THE PSYCHOLOGICAL WELL-BEING OF THE PRISON STAFF IN BULGARIAN PRISONS - Angelova, Natasha Virmozelova; Zaimova-Tsaneva, Emelina Valentinova; Dimitrova, Iva; Andonova, Gergana; Atanasova, Daniela; Karashtranova, Elena; Dzimbova, Tatyana; Manov, Boris (Psychological thought, 2025)
Working in prisons is associated with high levels of stress, which have a significant impact on the mental well-being of prison staff. This study examines the relationship between occupational stress, life satisfaction, and mental health of staff in Bulgarian prisons. Combining qualitative methods (in-depth interviews and focus groups), the study identifies the main factors influencing staff well-being. The results show that work-related stress contributes to anxiety, low life satisfaction, and security concerns. In addition, staff report health problems, including sleep disorders and an increased risk of chronic diseases. The data highlight the need to improve working conditions and provide psychological, legal, and health support. The article contributes to the understanding of the unique challenges faced by staff in the penitentiary system. These efforts are crucial to sustainable prison management and mitigating the negative impacts of stress on staff.